2017
DOI: 10.1182/bloodadvances.2017007112
|View full text |Cite
|
Sign up to set email alerts
|

Safety, pharmacokinetics, and reversal of apixaban anticoagulation with andexanet alfa

Abstract: Direct factor Xa (FXa) inhibitors lack a specific reversal agent for emergencies such as major bleeding or urgent surgery. Andexanet alfa, a modified, catalytically inactive, recombinant human FXa derivative, reverses anticoagulant effect by binding and sequestering FXa inhibitors. This original report of safety and dose-finding, phase 1 and 2 randomized, double-blind, placebo-controlled studies, investigated various doses of andexanet in healthy volunteers. Phase 1 evaluated the safety and pharmacokinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 34 publications
7
63
0
4
Order By: Relevance
“…The pharmacodynamic half-life of andexanet alfa is ≈ 1 h [36]. The reduction in anti-factor Xa levels was sustained during andexanet alfa treatment and the levels returned to placebo levels ≈ 2 h after the bolus or after the end of infusion [3235], which was consistent with the short pharmacodynamic half-life of andexanet alfa [36]. …”
Section: Scientific Summarymentioning
confidence: 70%
See 3 more Smart Citations
“…The pharmacodynamic half-life of andexanet alfa is ≈ 1 h [36]. The reduction in anti-factor Xa levels was sustained during andexanet alfa treatment and the levels returned to placebo levels ≈ 2 h after the bolus or after the end of infusion [3235], which was consistent with the short pharmacodynamic half-life of andexanet alfa [36]. …”
Section: Scientific Summarymentioning
confidence: 70%
“…apixaban, rivaroxaban, betrixaban, edoxaban and enoxaparin) in healthy volunteers [3235]. Following dosing with one of the factor Xa inhibitors, volunteers received andexanet alfa or placebo.…”
Section: Scientific Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…In the idarucizumab trial, thrombotic events occurred in 5.6% of patients after receiving therapy and included deep-vein thrombosis, pulmonary embolism, left atrial thrombus, myocardial infarction, and ischemic stroke (27). In the phase 2 trials of andexanet alfa in healthy volunteers, no thromboembolic events were reported (28). However, an interim analysis of the ongoing phase 3 trial in patients with acute major bleeding reported thrombotic events in 11% and death in 12% of patients within 30 days after administration (29).…”
Section: Benefits Versus Risks Of Doacs In Ckd 3 4 Andmentioning
confidence: 99%